Free Fatty Acids Increase Intracellular Lipid Accumulation and Oxidative Stress by Modulating PPARα and SREBP‐1c in L‐02 Cells. Issue 7 (7th June 2016) - Qin, Shumin; Yin, Jinjin; Huang, Keer
Abstract: Excessive fat accumulation and increased oxidative stress contribute to the pathogenesis of nonalcoholic fatty liver disease (NAFLD). However, the mechanisms underlying the development of steatosis are not entirely understood. The present study was undertaken to establish an experimental model of hepatocellular steatosis with a fat overaccumulation profile in which the effects of oxidative stress could be studied in L‐02 cells. We investigated the effects of free fatty acids (FFA) (palmitate:oleate, 1:2) on lipid accumulation and oxidative stress and their possible mechanisms in L‐02 cells. High concentrations of fatty acids significantly induced excessive lipid accumulation and oxidative stress in L‐02 cells, which could only be reversed with 50 μΜ WY14643 (the PPARα agonist). Immunoblotting and qPCR analyses revealed that FFA downregulated the expression of proliferator‐activated receptor alpha (PPARα), which contributed to the increased activation of sterol regulatory element binding protein‐1c (SREBP‐1c). These results suggest that FFA induce lipid accumulation and oxidative stress in L‐02 cells by upregulating SREBP‐1c expression through the suppression of PPARα.